Mistyka czy depresja? Noc ciemna św. Jana od Krzyża a noc psyche - Hornik, Paulina (Poznańskie Studia Teologiczne, 2015)
The dark night of the soul described by St. John of the Cross and depression are two different realities, but they can penetrate each other and occur at the same time. These two phenomena, although different, share many similarities. One and the other involves some suffering, some kind of disintegration. A breakdown of internal balance which the person may experience can be the basis for unity on a new level and the whole process can be crowned with reaching a new identity. The night of St. John of the Cross, although not identical with a disease state, can sometimes be a state of disorder that can be described as depression.